EFFECTS OF 12-WEEK WALKING BICYCLE EXERCISE ON AEROBIC CAPACITY AND LOWER LIMB MUSCLE STRENGTH IN MIDDLE-TO-OLDER AGED ADULTS WITH MILD METABOLIC DISORDERS: A CONTROLLED INTERVENTION STUDY - KUMAHARA, Hideaki; INUKAI, Yoshihide; SAKO, Akihito; SAITO, Seiji; MORIMURA, Kazuhiro; TAKATO, Jinro; AYABE, Makoto; OYAMA, Takashi (Japanese Journal of Physiological Anthropology, 2020)
The purpose of this investigation was to examine the effects of 12-week walking bicycle (WB) exercise on lower limb muscle strength and aerobic capacity in 16 middle-to-older aged adults with mild metabolic disorders. Of the 16 subjects, 8 completed the WB exercise (WB group); the remaining 8 subjects served as the control group. There were significant improvements in lower limb muscle strength and aerobic capacity in the WB group (p < 0.05) compared with the control group. The changes in lower limb muscle strength were significantly associated with the average duration of WB exercise (p < 0.05). These results suggest that WB exercise is a beneficial exercise modality and is associated with health benefits.